Company characteristics and opportunistic behaviour in Malaysian shariah-compliant companies / Muhammad Farhan Rosli, Radziah Mahmud and Nor Suhailati Abdul Manan - Rosli, Muhammad Farhan; Mahmud, Radziah; Abdul Manan, Nor Suhailati (2018)
Managerial opportunistic behaviour is normally viewed to have negative impact as managers have advantage to use information asymmetry to redistribute benefits from economic transactions unilaterally. In applying their estimates and judgements, managers may opportunistically manipulate earnings through adoption of accounting policies and accounting estimates. Consequently, there will be inefficient resource allocation which will affect companies' performance. Shariah-compliant companies are expected to engage in minimal earnings manipulation since they are bound by the Shariah rules. This study examines whether profitability, financial distress and leverage are determinants of opportunistic behaviour in Malaysian Shariah-compliant companies after controlling for the size and liquidity of the companies. This study is based on 110 companies in industrial product sector during 2012 till 2016. Applying agency theory, the results of this study confirm that Shariah-compliant companies with financial distress, high leverage and bigger size engage more in opportunistic behaviour.